A novel autonomous wireless sensor node for IoT applications - Ngan Nguyen; Quoc Cuong Nguyen; Minh Thuy Le (Universitas Ahmad Dahlan, 2019)
A novel wireless sensor network node (WSNN) is presented in this paper where the solar energy harvester system is used as an autonomous power solution for endless battery lifetime. In this sensor node, the meander-line Inverted-F-Antenna (MIFA) is proposed and integrated in a single -CC2650 chip of Texas Instrument. The simple structure, low cost, compact size, high efficiency and low power consumption are advantages of this single-chip WSNN. The experimental results show that MIFA antenna is promising solution to enhance communication performance in WSN. In addition, the investigated single-chip WSNN with multi-wireless technologies including Bluetooth Low Energy and Zigbee as well as 6LowPAN is an attractive device for internet of thing (IoT) applications.